Endoplasmic Reticulum Stress of Skeletal Muscle and Exercise Training Effects in Aging and Obesity - Nayoung Ahn; Jinho Koh; Kijin Kim (Asian Society of Kinesiology, 2018)
Endoplasmic reticulum (ER) stress associated with sarcopenic obesity in obesity and aging, which is a key factor in insulin resistance, are highly related. Long-term exercise training reduces ER stress via the activation of JUN N-terminal kinase (JNK) and reduction of nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκBα) decomposition and improves insulin resistance. Sarcopenia is associated with multiple factors, including increased pro-inflammation cytokine, oxidative stress, ER stress and fat infiltration as well as reduced mitochondrial function. Interaction between unfold protein response (UPR) and autophagy may play an important role to maintain the muscle protein quality control. The key factor in protein synthesis pathway for protein quality control is mammalian target of rapamycin complex 1 (mTORC1), indeed aging impairs contraction-induced human skeletal muscle mTORC1 signaling and protein synthesis. During exercise, mTOR pathway might be decreased that may result in an increase autophagy, because mTOR is a negative feedback factor for autophagy. Particularly, increased mTOR after exercise will be decrease autophagy. However, the effects of specific exercise training programs (type, intensity, time, frequency, etc.) and the mechanisms underlying these relationships are unclear. Therefore, it is necessary to establish the mechanisms of diabetes mellitus, focusing on sarcopenic obesity in obesity and aging, ER stress, and insulin resistance, and to analyze the effects of exercise training from a molecular biological perspective.